Management of University Social Responsibility: Advances, Perspectives, and Challenges (Docentes 2.0 Journal, 2026)
University Social Responsibility has become established over the last two decades as a fundamental component of the university's mission and a determining factor in institutional legitimacy. In this context, this essay aims to analyze the progress, perspectives, and challenges in its management during the period 2022-2025. The study employed an inductive method, within the humanistic-interpretive paradigm, with a qualitative, interpretive approach and a narrative-topical design, based on a comparative analysis of recent scientific literature. The strategies for institutional integration, curricular articulation, and stakeholder participation are examined, revealing progress in adopting frameworks aligned with international standards and implementing educational methodologies focused on developing ethical and civic competencies. However, persistent gaps remain in technology transfer, social appropriation of knowledge, and comprehensive evaluation metrics. Consequently, it is reaffirmed that the consolidation of University Social Responsibility requires strengthening its cross-cutting institutionalization, developing multidimensional evaluation frameworks, and consolidating inclusive communication that guarantees its sustainable impact.
Keywords: University social responsibility; sustainability; service-learning; educational management; sustainable development